The Effect of Sustainability Disclosure and Risk on Conservatism - Hartaima, Fadhila; Zuraida, Zuraida; Mulyany , Ratna (Winter Journal: IMWI Student Research Journal, 2025)
This study aims to examine the influence of sustainability disclosure, bankruptcy risk, litigation, market risk and reputational risk on conservatism. This study utilizes causal quantitative research methods. This research tests the established hypotheses and to look for the influence between the independent variable and the bound variable. The sample in this study is that all parts of the population used as the object of this research are companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 period that have met the criteria and use the slovin formula totaling 88 companies. The type of data source is in the form of secondary data. The data analysis used by the study was quantitative analysis using descriptive statistical calculation techniques and regression analysis. The results of the study simultaneously revealed sustainability, bankruptcy risk, litigation risk, market risk and reputation risk affect conservatism in non-financial companies. Partially, low sustainability disclosure can affect or decrease conservatism. An increased risk of bankruptcy can affect or enhance conservatism. A decreased risk of litigation can affect or decrease conservatism. Declining market risks can affect or increase conservatism. Increased reputational risk can influence or enhance conservatism.